Infrastructure model of the national insurance market of Кazakhstan - Müller, P.; Sembekov А.К.; Tyngisheva А.М. (BUKETOV BUSINESS REVIEW, 2017)
Effectiveness of the insurance market development is largely determined by the level of its infrastructure, which should act as a well-functioning mechanism with a developed system of information and analytical support, in combination with public authorities, insurance market entities and stakeholders. The insurance market infrastructure is a set of professional participants of the integration insurance space, who serve insurance activities, which contributes to the effective functioning of insurance and the quality provision of insurance services. The basis of the insurance market infrastructure consists of such entities as insurance companies, insurance intermediaries, government, self-regulatory organizations, the insurance payments guarantee fund, professional participants of the insurance market: surveyors, actuaries, adjusters, insurance ombudsman, etc. This article considers the actual features of the institutional structure of Kazakhstan’s insurance market, which affect the strengthening of the country’s competitiveness. In this context, the analysis of the existing Kazakhstan’s insurance market infrastructure was conducted. Based on the results of the study, the main directions of improvement of Kazakhstan’s insurance market infrastructure were proposed: creation of a single information center, improvement of the national reinsurance system, development of the insurance market in general. The authors developed a model of the infrastructure of the national insurance market, that meets the modern requirements of competitive markets – sales and the mechanism of social protection of the population, in the conditions of integrative interaction.